The Impacts of Nano-Micrometer Pore Structure on the Gas Migration and Accumulation in Tight Sandstone Gas Reservoirs - Juncheng Qiao; Xianzheng Zhao; Jianhui Zeng; Guomeng Han; Shu Jiang; Sen Feng; Xiao Feng (Energies, 2019)
The uncertainties between reservoir quality and gas migration and accumulation in tight sandstone gas reservoirs are intrinsically attributed to complex microscopic pore structures. Integrated analysis including the physical simulation experiment of gas migration and accumulation, X-ray computed tomography (X-CT), and casting thin section (CTS) were conducted on core plug samples collected from the Upper Paleozoic Permian Lower Shihezi and Shanxi tight sandstone of the Daniudi area in the Ordos Basin to investigate the impacts of pore structure on the gas migration and accumulation. Physical simulation suggested that the gas flows in migration in tight sandstone reservoirs were characterized by deviated-Darcy linear flow and non-linear flow regimes. Minimum and stable migration pressure square gradients determined by application of apparent permeability were employed as key parameters to describe gas flow. Pore structure characterization revealed that the tight sandstone reservoir was characterized by wide pore and throat size distributions and poor pore-throat connectivity. The pore−throat combinations could be divided into three types, including the macropore and coarse throat dominant reservoir, full-pore and full-throat form, and meso-small pore and fine throat dominant form. Comparative analyses indicated that pore and throat radii determined the gas flow regimes by controlling the minimum and stable migration pressure gradients. Gas accumulation capacity was dominated by the connected effective porosity, and the gas accumulation process was controlled by the cumulative effective porosity contribution from macropores to micropores. Variations in pore structures resulted in differences in gas migration and accumulation of tight sandstone reservoirs. The macropore and coarse throat-dominant and the full-pore and full-throat reservoirs exhibited greater gas migration and accumulation potentials than the small pore and fine throat dominate form.